2011
DOI: 10.1007/s00127-011-0364-x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health consumers and caregivers as instructors for health professional students: a qualitative study

Abstract: Providing students the opportunity to have contact with consumers with a mental illness in a safe, educational setting led to decreases in stigma, the fostering of empathy and self-reported behavior changes in practice. Sharing personal stories about mental illness is a powerful tool to decrease mental health stigma and may be an important aspect of a person's recovery from mental illness. Contact with mental health consumers in an educational setting is recommended, particularly for future health care profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 38 publications
3
89
0
Order By: Relevance
“…15 Therefore, it is undoubtedly important that pharmacists should create opportunities to foster empathetic behaviour toward the patients and learn to develop empathy in order to provide compassionate, patient-centered care. 6 At present, fostering and promoting empathy are believed ethical imperatives, and have been carried through the medical 16 and pharmacy 17,18 education to facilitate the interpersonal and philosophical development of healthcare students. The importance of displaying empathy during all healthcare interactions has been recognized and integrated in American pharmacy education.…”
Section: Introductionmentioning
confidence: 99%
“…15 Therefore, it is undoubtedly important that pharmacists should create opportunities to foster empathetic behaviour toward the patients and learn to develop empathy in order to provide compassionate, patient-centered care. 6 At present, fostering and promoting empathy are believed ethical imperatives, and have been carried through the medical 16 and pharmacy 17,18 education to facilitate the interpersonal and philosophical development of healthcare students. The importance of displaying empathy during all healthcare interactions has been recognized and integrated in American pharmacy education.…”
Section: Introductionmentioning
confidence: 99%
“…It could be hypothesised that hearing from service users and carers about experiences of distress resonated with psychologists on a personal level, creating an experience of 'state matching' as suggested in the empathy literature (de Waal, 2008), which may have led to enhanced empathetic understandings of service user and carer experiences as supported by previous research (Tew et al, 2012;Wood and Wilson-Barnett, 1999). Consistent with extant research, involvement appeared to help learners adopt person-centred approaches, taking into account the whole person, not just their problems (O'Reilly et al, 2012;Happell and Roper, 2003;Wood and Wilson-Barnett, 1999). The emotional resonance further seemed to create lasting memories of involvement experiences, a finding compatible with implicit learning theories (Dirkx, 2006).…”
Section: Discussionmentioning
confidence: 76%
“…With regard to changes in attitudes and practice, students reported that involvement made them see the person instead of the problem, broke down 'them-and-us' barriers, and helped understand service users and carer perspectives. Some studies found that a minority of students reported no impact of involvement (Happell and Roper, 2003;O'Reilly et al, 2012;Tew et al, 2012).…”
Section: Empirical Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these reports evaluated impact of "interventions" such as clerkship in psychiatry or specialized courses. Several studies by O'Reilly and colleagues (e.g., [15,16]) examined yet another way to address reducing the stigma of mental illness mostly among pharmacy students-providing the students the opportunity to have contact with consumers with a mental illness in a safe educational setting. They reported that such contact led to decreases in stigma.…”
mentioning
confidence: 99%